Profil Pasien Kanker Payudara Yang Menjalani Kemoterapi Di Rspal Dr. Ramelan Surabaya Periode Januari – Desember 2021 - SEKAR KURNIA CAHYA; ANANG MUFTI SUMARSONO; PRAWESTY DIAH UTAMI (Hang Tuah Medical Journal, 2024)
Background : Breast cancer is the most frequent cancer that occurs in Indonesia and becomes the main cause of mortality. Progression of breast cancer is affected by various factors, such as age, occupational status, menopause, estrogens, and lifestyle with high-fat dietary and alcohol consumption. Breast cancer progressivity may be stopped by surgery, chemotherapy, radiation, and hormonal therapy. Chemotherapy is an anticancer treatment management with the aim of killing cancer cells in the body and preventing recurrence and metastasis by administering cytotoxic agents. Chemotherapy may be performed previous to surgery (neoadjuvant) to achieve the decreased size of the tumor and facilitate the resection surgery. It may be performed as well after the surgery (adjuvant) to destroy any residual tumor cells. This study aimed to describe the profile of breast cancer patients who underwent chemotherapy from January to December 2021 at RSPAL Dr. Ramelan Surabaya. Methods: This study was descriptive with a retrospective design. Data collected from secondary sources of medical records patients with breast cancer in RSPAL Dr. Ramelan Surabaya from January to December 2021. Results: From the 79 samples, the most frequent age group in this study was a group of pre-elderly (45-59 years old). Most breast cancer patients are housewife. Breast cancer was commonly found in stage III. The most frequent chemotherapy management implemented for the breast cancer patient was adjuvant chemotherapy. Conclusion: women aged 45-59 years, not working, stage III, receiving adjuvant chemotherapy. Keywords : breast cancer, age, occupation, staging, chemotherapy